Enhancing the performance of heterogeneously coupled InAs Stranski-Krastanov on submonolayer quantum dot heterostructures. (November 2019) - Saha, Jhuma; Raut, Pravin; Ramavath, Rajkumar; Panda, Debiprasad; Das, Debabrata; Chakrabarti, Subhananda
Abstract: A detail investigation on enhancing the performance of heterogeneously coupled Stranski–Krastanov (SK) on Submonolayer (SML) quantum dot (QD) heterostructure has been done in this study. Different approaches have been implemented on the heterostructures to extend the emission wavelength towards telecommunication window. Strain reducing capping layers such as In x Ga 1-x As, In x Al y Ga 1-x-y As and GaAs 1-x Sb x has been considered for optimizing the discussed SK on SML QD heterostructures. Impact of different configurations on the hydrostatic and biaxial strain profile as well as carrier localization has been examined. Furthermore, by implementing these configurations, the photoluminescence wavelength was extended from the previously reported wavelength (1.1 μm) towards the telecommunication window (1.3 μm), which would impact the growth and fabrication of different optoelectronic devices in the near future. Highlights: Enhancing the performance of heterogeneously coupled SK on SML QD heterostructures. Implementing various capping configuration in both SK and SML QDs. Impact of combinational capping on SK on SML QD heterostructures. Effect of type-I and type-II band alignment on SK on SML QD heterostructures. Emission wavelength was extended towards telecommunication window (1.3–1.5 μm).